Surgeon General and segmental caesarean section. Indications and technique - Bazul, Víctor (2015)
This is a review of the indications, possibilities and limitations of the segmentarian cesarean operation, The author introduced this type of procedure in Peru in 1937; on the basis of his personal experience he has prepared this article directed not to the obstetrician but to the general surgeon faced with the necessity of this surgical treatment. Dr. Bazul remarks that this procedure has its better indication in the cases of placenta previa centralis, and advices about the type of anesthesia according to the status of both the mother and fetus.